A role for serotonin in the antidepressant activity of NG Nitro-L-arginine in the rat forced swimming test - Harkin, Andrew (My University, 2009)
The present study determined regional serotonin (5-HT) synthesis and metabolism changes associated with the nitric oxide synthase (NOS) inhibitor NG-nitro-L-arginine (L-NA) and the influence of 5-HT receptor blockade in the antidepressant-like actions of L-NA in the forced swimming test (FST). Regional effects of L-NA (5,10 and 20 mg/kg i.p.) on tryptophan hydroxylase (TPH) activity, the rate limiting enzyme for 5-HT synthesis, were determined by measuring accumulation of the transient intermediate 5-hydoxytryptophan (5-HTP) following in vivo administration of the amino acid decarboxylase inhibitor, NSD 1015 (100 mg/kg). L-NA (5-20 mg/kg) dose dependently increased 5-HTP accumulation, particularly in the amygdaloid cortex, following exposure to the FST. L-NA also provoked an increase in regional brain 5-HIAA concentrations and in the 5-HIAA:5-HT metabolism ratio. Co-treatment with NSD-1015 failed to consistently modify the antidepressant-like effects of L-NA in the FST. Sub-active doses of L-NA (1 mg/kg) and the 5-HT reuptake inhibitor fluoxetine (2.5 mg/kg) acted synergistically to increase swimming in the test. Co-treatment with the non-selective 5-HT receptor antagonist metergoline (1, 2 and 4 mg/kg), attenuated the L-NA (20 mg/kg)-induced reduction in immobility and increase in swimming behaviours. Metergoline alone however provoked an increase in immobility and reduction in swimming behaviours in the test. A similar response was obtained following co-treatment with the preferential 5-HT2A receptor antagonist ketanserin (5 mg/kg) and the 5-HT2C receptor antagonist RO-430440 (5 mg/kg). Co-treatment with the 5-HT1A receptor antagonist WAY 100635 (0.3 mg/kg) or the 5-HT1B receptor antagonist GR 127935 (4 mg/kg) failed to influence the antidepressant-like activity of L-NA. Taken together these data provide further support for a role for 5-HT in the antidepressant-like properties of NOS inhibitors.
PUBLISHED
Keywords: Antidepressant; Behaviour; Depression; Forced swimming test; Nitric oxide synthase; Serotonin